The impact of economic instruments on the auto industry and the consequences of fragmenting markets: Focus on the EU case - Luc Bastard (Organisation for Economic Co-operation and Development (OECD), Joint Transport Research Centre (JTRC), 2010)
This paper will focus on taxation issues addressing CO2 emissions in the European Union. When observing the different systems in place, a very broad diversity appears even with a cursory first glance. Actually, the diversity of taxation schemes among the Member States is such that it jeopardizes the concept of a Single Market in the European Union. Furthermore, this tax environment is not predictable. Even if the question of the efficiency of using such taxes to reduce CO2 emissions is put to one side, cost-effectiveness is an important issue, including in terms of the consequences for vehicle and component manufacturers.
Keywords: 330